From the early days of unmanned aerial vehicles (UAVS) to their integration into wireless networks - Miličević, Zoran M.; Bojković, Zoran B. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: This paper provides an overview of Unmanned Aerial Vehicles (UAVs) from their early days to their integration into modern wireless networks.Methods: It analyzes, synthesizes and compares the UAVs development technologies throughout their history with significant aspects of their integration in wireless communication networks.Results: Important aspects of wireless communications as one of the key technologies for UAVs are presented. Next, energy efficiency as a research path for UAVs is considered. The paper also emphasizes the present state in this area as well as what the future of UAVs in communications will be.Conclusion: UAVs are important not only for widespread military usage in various combat operations and warfare environment, but also for other purposes such as their integration in 5G networks.
Keywords: unmanned aerial vehicles (UAVs); drone swarm; Military Internet of Things (MIoT); bespilotne letelice (BL); roj bespilotnih letelica; vojne internet stvari